A multicenter, retrospective epidemiologic survey of the clinical features and management of bone metastatic disease in China. Issue 1 (25th April 2016) - Yang, Yunpeng; Ma, Yuxiang; Sheng, Jin; Huang, Yan; Zhao, Yuanyuan; Fang, Wenfeng; Hong, Shaodong; Tian, Ying; Xue, Cong; Zhang, Li
Abstract: Background: Bone metastases are common in patients with advanced cancer. Bisphosphonates (BPs) could prevent or delay the development of skeleton‐related events (SREs). The present study aimed to identify the clinical features of and treatment strategies for Chinese patients with bone metastases. Methods: Consecutive cancer patients who had bone metastases and received BP treatment were enrolled. A questionnaire was developed to collect the patients' clinical data, as well as information on the diagnosis and management of bone metastases. Physicians' awareness of the guidelines and knowledge of the application of BP were also assessed. Results: A total of 3223 patients with lung cancer (36.5%), breast cancer (30.9%), prostate cancer (8.5%), and gastrointestinal cancer (5.7%) were included in this study. The sites of bone metastases were the thoracic spine (56.0 %), lumbar spine (47.1%), ribs (32.6%), and pelvis (23.2%). The SRE frequency was the highest in patients with multiple myeloma (36.6%), followed by those with lung cancer (25.9%), breast cancer (20.2%), prostate cancer (18.2%), and gastrointestinal cancer (17.3%). Irradiation to the bone was the most frequent SRE (58% in lung cancer patients, 45% in breast cancer patients, and 48% in prostate cancer patients). Our survey also showed that 45.5% of patients received BP within 3 months after their diagnosis of bone metastases, whereas the remaining 54.5% of patients did not receive BP treatment until at least 3 months after their diagnosis of bone metastases. The SRE frequency in the former group was significantly lower than that in the latter group (4.0% vs. 42.3%, P < 0.05). In patients with more than 6 months of continuous BP treatment, the mean time to the first SRE was significantly longer than that in patients with less than 6 months of continuous BP treatment (7.2 vs. 3.4 months, P < 0.05). In addition, 12.2% of the physicians were not aware of the efficacy of BP in preventing and delaying SRE. Only half (52.3%) of the physicians agreed that the BP treatment should persist for at least 6 months unless it was intolerable. Conclusions: Our study suggested that prompt and persistent BP treatment was associated with a reduced risk of SREs. However, our survey also revealed that the proper application of BP was not as common as expected in China.